2016
DOI: 10.1002/jbmr.2805
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Proximal Femur Fractures in a Teenager With Osteogenesis Imperfecta on Continuous Bisphosphonate Therapy: Are We Overtreating?

Abstract: Long-term bisphosphonate (BP) therapy in adults with osteoporosis is associated with atypical femoral fractures, caused by increased material bone density and prolonged suppression of bone remodeling which may reduce fracture toughness. In children with osteogenesis imperfecta (OI), long-term intravenous BP therapy improves bone structure and mass without further increasing the already hypermineralized bone matrix, and is generally regarded as safe. Here we report a teenage girl with OI type IV, who was starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…However, it is still unclear whether the effects of bisphosphonates on bone metabolism are favorable for bone regeneration and bone material properties on a molecular level, particularly when considering the need for long‐term treatment regimens. Furthermore, the apparent significant decrease in the incidence of fractures associated with bisphosphonates remains a matter of debate . Hence, the bone‐remodeling‐based concept of anti‐sclerostin treatment may provide a promising approach to cover relevant treatment periods as part of a long‐term medication strategy that enables phases of bone regeneration and formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear whether the effects of bisphosphonates on bone metabolism are favorable for bone regeneration and bone material properties on a molecular level, particularly when considering the need for long‐term treatment regimens. Furthermore, the apparent significant decrease in the incidence of fractures associated with bisphosphonates remains a matter of debate . Hence, the bone‐remodeling‐based concept of anti‐sclerostin treatment may provide a promising approach to cover relevant treatment periods as part of a long‐term medication strategy that enables phases of bone regeneration and formation.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have struggled to determine any true benefit in terms of fracture rate, quality of life or mobility in patients with OI on bisphosphonate treatment 21 22. Concerns have also been raised about the long-term use of bisphosphonates, particularly with regard to the risk of atypical femur fracture in OI 23. This study’s finding of one or more potential inflammatory pathways active in OI could help in the development of more targeted and effective treatments for OI.…”
Section: Discussionmentioning
confidence: 89%
“…In this series, 14/16 femoral fractures in the bisphosphonate-treated cohort occurred within the subtrochanteric location, in contrast to a widespread fracture pattern in the historical controls [5]. Hegazy et al reported a series of 6 bisphosphonate-treated children with OI who sustained minimally traumatic subtrochanteric and diaphyseal femoral fractures over preexisting intramedullary rods [4], and Vasanwala et al similarly reported an adolescent OI patient with recurrent, atraumatic femoral fractures following bisphosphonate treatment [6]. The contribution of the underlying collagen defect in the development of femoral fractures in these series is unknown, and to our knowledge there have been no reports of subtrochanteric femoral fractures in non-OI children treated with bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…Case series of children with osteogenesis imperfecta (OI), a disorder of bone fragility due to abnormalities in type I collagen, report a potential association between bisphosphonate treatment and proximal femoral fractures [46]. To date, there have been no reports of AFFs in children or adolescents without primary collagen defects.…”
Section: Introductionmentioning
confidence: 99%